THE RHETORIC OF BODY, CLOTHING AND IDENTITY IN THE VITA AND GENESIS - Neufeld, Dietmar (Scriptura, 2005)
This paper will concentrate on the dynamic relationship between body, clothing, and identity. Nakedness and clothing mark the bodies of Adam and Eve with religious, political, and social distinction and other forms of embodied social meaning such as the transition from one state to another, the transformation of bodies of honour to bodies of shame, and the refashioning of the conduits of God’s power who is not about to countenance challenges to his honour as benefactor of the cosmos and humankind (Porter 1999, 4). In addition, the surfaces of their bodies are a significant site for the production and display of difference and their physical transformations and regulations essential to maintaining and regulating ancient Israel’s power structures and social organization (Esler 2001, 26-30). In the Vita and Genesis, the management of the bodies of Adam and Eve is integral to the maintenance and definition of social relationship and rank between God and humans, desires, and social identities.